Varietal responses of pigeon pea (Cajanus cajan (L.) Millsp.) to application of compost (2020)
Compost use is one of the most important factors, which contribute to increased productivity and sustainable agriculture. The study was carried out at the screen house of the Institute of Agriculture Research and Training (I.A.R&T), Ibadan to evaluate the effects of different levels of compost fertilizer on the growth and yield on three varieties of pigeon pea; A-NSWCC 24, B-NSWCC 29A and C-NSWCC 34D). Compost (Poultry manure + Mexican Sun flower) was applied in 0 tha-1, 5 tha-1, 10 tha-1and 15 tha-1. Growth data were collected based on days to flowering, 50% and 100 % flowering, plant height, stem height, number of leaves and stem diameter. Yield parameters were collected based on pod length, number of seeds per pod, pod weight, grain yield kg ha-1, 100 seed mass (g) were sampled when the pods were matured. All data collected were subjected to Analysis of Variance using Genstat statistical package (2013) and treatment means separated using Least Significant Difference (LSD) at P=0.05. The result obtained showed the highest mean number of leaves was obtained in the compost 5 tha-1on variety A (272.33) leaves. From the result considering grain weight, seed weight harvested/plot, 100 seed weight, number of seeds/pod and days to flowering the sorting order results indicated that the best mean performance was obtained in 15 tha-1 compost application on variety A. The application of the compost has significant effect on the three varieties and therefore can be recommended for cultivation of pigeon pea.